Understanding Islamic-oriented non-governmental organisation and how they are contrasted with NGO in outdoing Malaysia LGBT phenomenon - Jaffary Awang; Muhamad S. Abdul Aziz; Nur F. Abdul Rahman; Mohd I. Mohd Yusof (HTS Teologiese Studies/Theological Studies, 2023)
The term non-governmental organisations (NGOs) has been well-known for the development of human rights, charity works and organisational developments. On the other hand, some NGOs also have their specialised roles to help the community such as in conflict resolution, cultural preservation, policy analysis and information provision. Apart from that, there are many categories of NGOs: Islamic-oriented non-governmental organisation (IONGOs), faith-based organisation (FBO), humanitarian NGOs (HNGOs) and government organised NGOs (GONGOs). However, in this research, the researchers focus on how IONGOs compare with NGOs in assisting the lesbian, gay, bisexual, and transgender (LGBT) community based on four hijrah NGOs: Persatuan Islah Movement, Persatuan Insaf Pahang, Hijrah Republique Network and Usrah Iqrak. These four NGOs were chosen because of their roles in assisting the LGBT community. In this research, the researchers adapt the qualitative research by using a case study method; phenomenological approaches and a document analysis have also been applied as well. The result shows that these four IONGOs are different from the NGOs based on the seven typologies applied: intersection, distinct, substantive, subset, co-existing, atomistic grouping and constitutive. The implications of this article highlight the fact that IONGOs are different from the LGBT NGOs in Malaysia as they focus more on spirituality and an Islamic pathway. Hence, future research should include focus group interviews with all the members in NGOs that assist the LGBT hijrah in the community.